2021
DOI: 10.1021/acs.jafc.1c03794
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin and Allicin Can Alleviate the Hepatotoxicity of Lead (Pb) through the PI3K Signaling Pathway

Abstract: Lead (Pb) is a common toxic heavy metal pollutant in the environment that seriously endangers the health of animals. The liver is a key target organ affected by Pb toxicity. Plant extracts allicin and quercetin have a strong antioxidant capacity that can promote the excretion of heavy metals by improving the body’s antioxidant defense and chelating heavy metal ions. To explore the preventive and therapeutic effects of allicin and quercetin on Pb poisoning in chickens, 96 chickens were randomly divided into eig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…[35] Also, myricitrin, myricetin, and quercetin could alleviate liver injuries by suppressing oxidative stress, inflammatory responses, and hepatocellular apoptosis. [36][37][38] Kaempferol was shown to prevent alcoholic liver injuries in mice by increasing the levels of butyrate receptors and tight junction proteins in the intestinal mucosa. [39] CCl 4 -induced lipid peroxidation of the hepatocellular membrane is a key factor leading to liver injuries.…”
Section: Discussionmentioning
confidence: 99%
“…[35] Also, myricitrin, myricetin, and quercetin could alleviate liver injuries by suppressing oxidative stress, inflammatory responses, and hepatocellular apoptosis. [36][37][38] Kaempferol was shown to prevent alcoholic liver injuries in mice by increasing the levels of butyrate receptors and tight junction proteins in the intestinal mucosa. [39] CCl 4 -induced lipid peroxidation of the hepatocellular membrane is a key factor leading to liver injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that the allicin has a variety of biological activities, its chemical and thermal instability has prompted efforts to develop new drugs for therapeutic development . Furthermore, allicin and derivatives have rich biological activities in antiparasitic, acaricidal, , anti-inflammation, antioxidative, insecticidal, and anticancer field, and allicin can also promote intestinal health and development …”
Section: Introductionmentioning
confidence: 99%
“…8 Despite the fact that the allicin has a variety of biological activities, its chemical and thermal instability has prompted efforts to develop new drugs for therapeutic development. 9 Furthermore, allicin and derivatives have rich biological activities in antiparasitic, 10 acaricidal, 11,12 anti-inflammation, 13 antioxidative, 14 insecticidal, 15 and anticancer 16 field, and allicin can also promote intestinal health and development. 17 In addition, three pyridine-N-oxide alkaloids (Figure 1, compound 1−3) containing disulfide bond functional groups were isolated from Allium stipitatum, which were potentially an inhibitor of fatty acid biosynthesis and exhibited MICs of 0.5− 8 μg/mL against Mycobacterium tuberculosis and methicillinresistant Staphylococcus aureus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preclinical studies have shown that allicin has positive impact on the healing of wound under diabetic conditions and streptozotocin-induced nephropathy in Wistar rats [ 23 , 24 ]. It has also shown the ability to alleviate hepatic toxicity induced by lead (Pb) and acrylamide [ 25 , 26 ]. Allicin has been reported to recover the spermatogenesis and sperm quality after diabetic induced damage, it has also shown beneficial effects on the reproductive system of male Wistar rats [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%